2014
DOI: 10.1364/ol.39.004294
|View full text |Cite
|
Sign up to set email alerts
|

Stable radio-frequency phase distribution over optical fiber by phase-drift auto-cancellation

Abstract: We report a new radio-frequency (RF) phase stabilization approach for long-haul optical fiber distribution. The phase drift of an RF signal induced by fiber-length variations can be canceled out automatically via RF mixing without using active phase discrimination and dynamic phase tracking. A key significance of our approach is that no assistant local oscillator (LO) signal is needed. Consequently, frequency estimation of the received RF signal, as well as frequency locking between the LO and the received RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In an experiment, a 6-GHz RF signal is Fig. 4 Schematic diagram of the post-phase correction scheme without any auxiliary signal [39]. FD frequency divider transmitted over 20-km SMF with a root mean square (RMS) timing jitter of 1.33 ps.…”
Section: Post-phase Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experiment, a 6-GHz RF signal is Fig. 4 Schematic diagram of the post-phase correction scheme without any auxiliary signal [39]. FD frequency divider transmitted over 20-km SMF with a root mean square (RMS) timing jitter of 1.33 ps.…”
Section: Post-phase Correctionmentioning
confidence: 99%
“…The idea is demonstrated by Li et al [39] with the schematic diagram shown in Fig. 4, by which passive phase correction without any reference source is realized.…”
Section: Post-phase Correctionmentioning
confidence: 99%
“…These schemes can greatly reduce the phase jitter, with the advantage of low noise. However, the phase recovery time will be limited to the proportional integral derivative algorithm [12], [13], and the complex feedback control circuits are indispensable. In other compensation schemes, the phase jitter is passively compensated by electric [12]- [16] or microwave photonic [17] frequency mixing based on phase conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…Applying feedback loop is the most commonly used approach to realize stable phase transfers in these applications [9], in which the phase error extracted between the reference signal and the optical fiber link round-trip signal is used to control electrical or optical modules (e.g., optical/electrical delay lines [10], fiber stretchers [11], and voltage-controlled oscillators (VCOs) [12]) for phase fluctuation cancellation. Recently, another approach named passive frequency mixing is proposed to realize stable phase transfers for clock disseminations [13]- [15], or downlink radar arrays [5], [9], [16], with the merits of rapid and endless post error cancellation, and obvious electronic complexities reduction. Until now, the schemes based on passive mixing are only used for the stable phase transfers of CW RF signals in uplink or downlink, however, stable phase transfers for pulsed RF signals and in both uplink and downlink are also required in uplink radar arrays.…”
Section: Introductionmentioning
confidence: 99%